Моделювання термомеханічних властивостей неферомагнітних електропровідних тіл з плоскопаралельними границями за дії імпульсних електромагнітних полів при врахуванні розсіювання енергії - Мусій, Роман; Стасюк, Галина; Шимчак, Йосиф (КІНПАТРІ ЛТД, 2013)
The methodology for investigating thermostressed state and carrying capacity of non ferromagnetic conductive solids with plane parallel boundaries under specific types of pulse amplitude modulated EMF.
Modeling thermomechanical properties nonferromagnetic conductive bodies with planar boundary for the pulse of electromagnetic fields taking into account energy dissipation